Can Cryptogonimids of the Same Genus Influence Each Other’s Level of Genetic Variation? - Ekaterina S. Tokarskaya; Yulia V. Tatonova; Haneef Ahmed Amissah; Polina G. Shumenko; Mikhail Yu. Shchelkanov (Biology)
Trematodes of the genus Exorchis are parasites that are common in East and Southeast Asia. These parasites are known to infect fish, thus impacting aquaculture significantly. An introspection into the dynamics of infection of these parasites has revealed possible co-infection in shared hosts. But data on the dynamics of their shared host on their population structure and genetic variability is lacking. In this study, we investigate the intraspecific structure of the Exorchis species, Exorchis oviformis, and E. convictus, both of which coexist in the same definitive host. By using partial gene sequences of the mitochondrial cox1 gene (715 bp), including 30 newly obtained sequences from the southern part of the Russian Far East, we found a low level of genetic variation in both species, consistent with previous findings of other trematodes from the same region. We hypothesize that the observed low variability could be attributable to the process of host infection and transmission and abiotic factors influencing a recent decline in host variability and abundance. This is driving a strong selection pressure due to the limited number of parasites reaching the definitive host. This, among other factors, could possibly impact the long-term survival and adaptability of Exorchis and other trematodes at large in the region. However, we also believe that there may be a chance that these closely related species could exert an influence on each other’s genetic diversity, potentially limiting the variation within each species. To uncover the dynamics driving these observations, we propose the approach of expanding sampling, broader genetic marker analyses, and investigations of varied host populations that could elucidate the complexities of the Exorchis species genetic variability and evolutionary dynamics.